PENGARUH LATIHAN OPERAN TOSSBACK (WALL) TERHADAP KEMAMPUAN CHEST PASS TEAM BOLA BASKET PUTRA SMAN 1 PEKANBARU - Pradana, Yoga Arya; Ramadi, Ramadi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The problem in this research is lack of chest pass at doing passing on basketball boys team SMAN 1 Pekanbaru. According to the problem the writer conduct Tossback (wall) pass exercise, to know the effect of tossback (wall) pass exercise towards chest pass on the basketball boys team SMAN 1 Pekanbaru. In order that, chest pass reach maximum result. This reasearch is an experimental research, research design is one group pretest-posttest. The population in this research is basketball team SMAN 1 Pekanbaru which consist of 11 people. Technique sampling that is used is total sampling which is all population of basketball boys team SMAN 1 Pekanbaru. The instrument that given to tosback (wall) pass is wall pass test. After that the data is analyze with statistical way to test the normality with lilifors test on significant phase Î± (0,05). The Hyphotesis that is proposed is the effect of tossback (wall) pass to wards the chest pass. Based on the results of the analysis resulted in pretest tossback (wall) the average of 12,36 and the average posttest of 16,36 with an increase of 4,0. According to T test, produce a result thitung 6,8 and ttable 1,81, it means that thitung > ttable . Therefore, there is effect of tossback (wall) pass exercise towards chest pass at dpoing passing on basketball boys team SMAN 1 Pekanbaru.Keywords : Tossback (wall), Chest Pass